Tiktok Poison Against the Consumerist Culture of Madiun City People in The Era of Digital Disruption - Yopie Diondy Kurniawan; Halleina Rejeki Putri Hartono; Amri Amrulloh; Qimyatusaadah, Qimyatusaadah (Tinta Emas Institute, 2023)
The COVID-19 pandemic, which has become an outbreak since December 2019, has changed the order of world life. Social activities that are usually carried out in person have to be carried out online, including working, studying and shopping. This causes the use of social media to increase, one of which is the TikTok application. In the TikTok application, there is a trend that is of interest to social media users, namely TikTok poison. Poison TikTok is a trend that displays content containing information about a product, such as unboxing or interesting reviews, so that it attracts the interest of the audience to shop online. This can certainly have an impact on the level of consumerism of social media users. Therefore, the aim of this research is to find out how the toxic trend of TikTok influences and its relationship to consumer behavior in the millennial generation. From this research it is known how student behavior, the impact obtained, students' responses and reasons for TikTok poison influence their level of consumerism.